2018
DOI: 10.1002/jcb.27518
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamic alterations regulate melanoma cell progression

Abstract: Research on mitochondrial fusion and fission (mitochondrial dynamics) has gained much attention in recent years, as it is important for understanding many biological processes, including the maintenance of mitochondrial functions, apoptosis, and cancer. The rate of mitochondrial biosynthesis and degradation can affect various aspects of tumor progression. However, the role of mitochondrial dynamics in melanoma progression remains controversial and requires a mechanistic understanding to target the altered meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…4,19 Mdivi-1 increased OCR in non-cancer cells like mouse neuroblastoma 58 but deceased OCR in human ductus arteriosus smooth muscle cells. 59 Similar to these findings, studies showed that mdivi-1 increased OCR in some cancer cells 60,61 but decreased OCR in other cancer cells. 25,62 To better understand the regulatory role of DRP1 in cancer metabolism, we used [U- 13 C] glucose tracing to directly reveal the intracellular glucose metabolism in DRP1-deficient H460 lung cancer cells and in multiple mdivi-1-treated cancer cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…4,19 Mdivi-1 increased OCR in non-cancer cells like mouse neuroblastoma 58 but deceased OCR in human ductus arteriosus smooth muscle cells. 59 Similar to these findings, studies showed that mdivi-1 increased OCR in some cancer cells 60,61 but decreased OCR in other cancer cells. 25,62 To better understand the regulatory role of DRP1 in cancer metabolism, we used [U- 13 C] glucose tracing to directly reveal the intracellular glucose metabolism in DRP1-deficient H460 lung cancer cells and in multiple mdivi-1-treated cancer cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…It is worth noting that the higher expression of Mfn2 has also been reported in lung adenocarcinoma tissues as compared to adjacent normal tissues, and Mfn2 knockdown results in impaired cancer cell proliferation (81). In ovarian cancer (82), breast cancer (83), and melanoma (84), Mfn2 knockdown suppresses oxygen consumption rate (OCR). In pancreatic cancer cells (PANC-1), Mfn2 knockdown enhances mitochondria-dependent energy metabolism by promoting activity of electron transport chain complexes (85).…”
Section: Mitochondrial Fusion and Fission Shape Cancer Metabolismmentioning
confidence: 99%
“…Mitochondrial fission and fusion are essential processes that require many specific proteins, including the mechanical enzymes, which physically alter the mitochondrial membrane, and adapter proteins, which modulate the interaction of these mechanical proteins with organelles. The fusion proteins, including mitofusins (MFN1, MFN2) and optic atrophy (OPA1), as well as fission proteins, including mitochondrial fission 1 (FIS1) and dynamin-1-like (DRP1), play an important role in the dynamic changes of the mitochondria 19 , and although incompletely understood, mitochondrial morphological changes appear to be involved in several activities critical to cell health and tumor cells 20 . Based on cellular process involvement, mitochondrial dynamic imbalance may be responsible for the mitochondrial dysfunction of many diseases.…”
mentioning
confidence: 99%